Widespread tropical agrowastes as novel feedstocks for biochar production: characterization and priority environmental uses - Chin Pampillo, Juan Salvador (2020)
Biochar, a carbon-rich pyrolytic product, has demonstrated positive results as a soil improver and carbon sequestration agent. Its production could be an appropriate and innovative practice for agricultural waste management in the context of environmentally smart agriculture. However, considering the relevant effect of the production conditions on the final biochar properties, its characterization is a necessary step, moreover, if an unknown feedstock is being used. Coffee hulls (CH), pineapple stubble (PS), and palm oil fiber (PF) are typical tropical agro-industrial wastes, and biochar from the first two are not reported before. In this work, biochars from them were obtained after 1 h of pyrolysis at 600 °C. Surface area and pH of biochars were close to 60 m2g−1 and 9, respectively (except for PF which was 29 m2g−1), while torrefied biomass (charred material prepared at 300 °C) presented a surface area close to 1 m2g−1 and neutral pH. Fixed C was approximately 80% (PF and CH) and 59% (PS) for biochars and close to 40% in torrefied biomass. It was concluded that key properties of biochars were mostly determined by the feedstock’s origin. Due to its high ash content and surface area, PS biochar was identified as a suitable soil amendment, while PF and CH biochars showed a higher potential for carbon sequestration in soil due to their high fixed carbon content, demonstrating that the production of biochars from widespread tropical wastes tailored for specific environmental uses is possible.